Interprofessional Education Small Group: A 25-Year-Old-Man with Dyspnea, Productive Cough, and Chest Tightness - Rob Zachow; David Riley; Joe Schwenkler (Association of American Medical Colleges, 2014)
Abstract Introduction This simulation case was developed for use as part of the Rutgers-Robert Wood Johnson Medical School interprofessional education initiative. It was designed to foster the health care team approach among first-year medical, physician assistant, and pharmacy students. The case describes a man with mild intermittent asthma who presents to the emergency department due to an exacerbation. Methods Six discussion topics were designed for use in a small-group teaching environment. These explore various aspects of asthma, including its pathophysiology, effect on normal pulmonary physiology, medical management (i.e., pharmacology), and follow-up care. A postsession survey was disseminated to all students. Results When asked to rate the statement "Overall in terms of reinforcement of concepts, and integration of course material, and conveying a health care team approach to problem solving, this small-group session met my learning needs" on a 5-point Likert scale (strongly disagree = 1, strongly agree = 5), students responses were: 3.8% (n = 4) strongly disagree, 17.1% disagree (n = 18), 24.8% neutral (n = 26), 44.8% agree (n = 47), 9.5% strongly agree (n = 10). The Likert average for all responses (N = 105) was 3.4. Discussion Student comments indicate that this modality served both the interprofessional education and didactic objectives of this small group. In addition, this session promoted professional interactions, which otherwise may not have occurred, between the faculty within the representative schools.